Opinion Leadership and the Perceived Health Benefits of Local Food - Layne S. Marshall; Melissa R. Taylor; Alexa J. Lamm (EDIS)
This EDIS document is the first in a series discussing how Extension can more efficiently encourage citizens to join the local food movement by effectively utilizing and leveraging opinion leaders. These articles look at the role opinion leaders, or individuals who have a large amount of influence within their respective social circles, can have on motivating their peers to join in purchasing local food. Written by Layne S. Marshall, Melissa R. Taylor, and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, August 2016.